Distinct effect of actin cytoskeleton disassembly on exo- and endocytic events in a membrane patch of rat melanotrophs - Chowdhury, Helena H (Blackwell Science Inc, 2002)
We used the cell-attached mode of patch-clamp technique to measure discrete attofarad steps in membrane capacitance (C(m)), reporting area changes in the plasma membrane due to unitary exocytic and endocytic events. To investigate the role of the actin cytoskeleton in elementary exocytic and endocytic events, neuroendocrine rat melanotrophs were treated with Clostridium spiroforme toxin (CST), which specifically depolymerises F-actin. The average amplitude of exocytic events was not significantly different in control and in CST-treated cells. However, the amplitude of endocytic events was significantly smaller in CST-treated cells as compared to controls. The frequency of exocytic events increased by 2-fold in CST-treated cells relative to controls. In control cells the average frequency of exocytic events (ν(exo)) was lower than the frequency of endocytic events (ν(endo)) with a ratio ν(exo)/ν(endo) < 1. In the toxin treated cells, the predominant process was exocytosis with a ratio (ν(exo)/ν(endo) > 1). To study the coupling between the two processes, the slopes of regression lines relating ν(exo) and ν(endo) in a given patch of membrane were studied. The slopes of regression lines were similar, whereas the line intercepts with the y-axis were significantly different. The increased frequency of unitary exocytic events in CST-treated cells is consistent with the view, that the actin cytoskeleton acts as a barrier for exocytosis. While the disassembly of the actin cytoskeleton diminishes the size of unitary endocytic events, suggesting an important role of the actin cytoskeleton in determining the size of endocytic vesicles, the coupling between exocytosis and endocytosis in a given patch of membrane was independent of the state of the actin cytoskeleton.